2021
DOI: 10.1002/ecy.3500
|View full text |Cite
|
Sign up to set email alerts
|

Top predator introduction changes the effects of spatial isolation on freshwater community structure

Abstract: Current conceptual metacommunity models predict that the consequences of local selective pressures on community structure increase with spatial isolation when species favored by local conditions also have higher dispersal rates. This appears to be the case of freshwater insects in the presence of fish. The introduction of predatory fish can produce trophic cascades in freshwater habitats because fish tend to prey upon intermediate predatory taxa, such as predatory insects, indirectly benefiting herbivores and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…and 480 m from a source wetland (Pelinson et al, 2021). We found that a 120-m isolation distance was sufficient to impose a significant dispersal limitation on pond communities, preventing colonization by several insect taxa.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…and 480 m from a source wetland (Pelinson et al, 2021). We found that a 120-m isolation distance was sufficient to impose a significant dispersal limitation on pond communities, preventing colonization by several insect taxa.…”
Section: Discussionmentioning
confidence: 79%
“…As a result, the hostile abiotic condition experienced in the waterbody is also experienced in many, if not all neighbouring waterbodies, creating strong spatial effects tied to land use that manifest as a limited pool of species capable of colonization. That strong spatial effects in addition to local unfavourable conditions are linked to these biodiversity declines is suggested by another field experiment in which we followed freshwater community assembly in mesocosms constructed at 30, 120 and 480 m from a source wetland (Pelinson et al, 2021). We found that a 120‐m isolation distance was sufficient to impose a significant dispersal limitation on pond communities, preventing colonization by several insect taxa.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, wide interfluves (i.e. >500 m) generally benefit all herbivore and detritivore taxa (Pelinson et al, 2021), being more effective stepping stones for them. However, such an effect can be attenuated or even interrupted for some non-predatory taxa if ponds are contaminated by insecticides as these taxa can take longer to recover from insecticide pulses in isolated communities.…”
Section: Effect Of Fertilizers In Different Spatial Contextsmentioning
confidence: 99%
“…dragonflies and aquatic beetles), they have smaller populations and longer generation times than many herbivores and detritivores (i.e. midges and mosquitoes); thus, predators have fewer events of dispersal, which result in lower abundances in isolated habitats when compared to more connected ones (Chase & Shulman, 2009; Pelinson et al, 2021). Additionally, because pesticides are usually applied in seasonal pulses, their direct acute effects, albeit strong, can be temporary—provided that connectedness allows full or partial recovery of the original community structure (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation